Analisis Pengaruh Tilting Antenna Terhadap Coverage Area Jaringan 4G LTE (Studi Kasus Kecamatan Trenggalek) - Rizal Aji Istantowi (Politeknik Negeri Malang, 2019)
4G LTE networks in big cities are already well available. Meanwhile, on small to medium-sized cities, the 4G LTE network is not evenly distributed and maximized. This study chooses the variable tilting antenna to the coverage area, because in sending information from a base station using an antenna. The average RSRP value (dBm) of the existing base station in the calculation with a distance of 200 m is -122.90 dBm, a distance of 500 m is -136.79 dBm, and a distance of 1000 m -147.30 dBm. Meanwhile, in the simulation with a distance of 200 m of -108.22 dBm, a distance of 500 m of -121.81 dBm, and a distance of 1000 m of -132.69 dBm. The coverage area value of the existing base station in the calculation is 5.29%, while in the simulation it is 11.18%. The average RSRP value (dBm) at optimal conditions for calculations at a distance of 200 m is -80.13 dBm, at a distance of 500 m is -94.03 dBm and at a distance of 1000 m is -104.56 dBm. Meanwhile, the simulation at a distance of 200 m is -98.09 dBm, at a distance of 500 m is -112.79 dBm and at a distance of 1000 m is -123.31 dBm. The value of the coverage area for the calculation is 20.32%, while for the simulation it is 15.01%. The current need for base stations in Trenggalek District that has been met is 68%.